Identifikasi Gaya Belajar Berdasarkan Gender dengan Hasil Belajar IPA - Juariah Fitri; Tri Jalmo; Rini Rita T Marpaung (Universitas Lampung, 2017)
The studys aim were to find the characteristics of learnig style, the different based on gender and the correlation with science learning achievement. This study was descriptive. Samples were 318 of 64% VII grade students in Labuhan Ratu, that using purposive sampling. Research data were laerning style and learning achievement that were obtained from questionnaires and tests. Data were analyzed descriptively and statistically using Mann Whitney U different test and Kendalls Tau correlation test. As a result, there are three learning styles was visual, auditory, and kinesthetic. The dominant learning styles of the students was auditory. The difference between learning styles and gender was not significant and the correlation between learning styles to learning achievement was low level of the relationship